Gadofluorine m uptake in stem cells as a new magnetic resonance imaging tracking method: an in vitro and in vivo study - Giesel, Frederik L.; Stroick, Mark Gregor; Griebe, Martin; Tröster, Helmut; von der Lieth, Claus W.; Requardt, Martin; Rius, Maria; Essig, Marco; Kauczor, Hans-Ulrich; Hennerici, Michael G.; Fatar, Marc (Investigative radiology, 2006)
OBJECTIVES: Cell tracking using ultrasmall iron particles is well established in magnetic resonance imaging (MRI). However, in experimental models, intrinsic iron signals derived from erythrocytes mask the labeled cells. Therefore, we evaluated Gadofluorine M with other gadolinium chelates for a T1-weighted positive enhancement for cell tracking in vitro. In addition, Gadofluorine M was tested in vivo. - MATERIAL AND METHODS: Gadofluorine M and other gadolinium chelates were used to label stem cells with and without uptake-mediating agents in vitro and in vivo using a 1.5 T MRI. In addition, histology and molecular modeling was investigated. - RESULTS: Gadofluorine M revealed comparable properties to an uptake mediating agent in molecular modeling. Without an uptake-mediating agent Gadofluorine M-labeled cells were detected as a T1-weighted positive contrast in vitro and in vivo. Histology confirmed a 100% success rate for intracellular labeling. - CONCLUSION: This study describes a novel contrast agent with the capability of intracellular accumulation without an uptake mediator providing a T1-positive MRI signal at 1.5 T and may be suitable for cell tracking in animal models with intraparenchymal hemorrhages such as stroke or malignant tumors.